The Advantage of NoSQL Databases over SQL Databases - Mario-Tudor CHIRIAC (Database Systems Journal, 2025)
This article highlights the advantages of NoSQL databases compared to traditional SQL (relational) databases. It argues that the database concept is often implicitly tied to relational models, overlooking non-relational databases’ potential in Big Data, data analysis, and AI. Non-relational databases offer schema flexibility, horizontal distribution, and high read/write speeds—critical for processing very large data volumes efficiently.